IDENTIFIKASI AIR TANAH DI PERUMAHAN GRAHA MUSTAMINDO PERMAI 3 MENGGUNAKAN METODE GEOLISTRIK RESISTIVITAS KONFIGURASI SCHLUMBERGER - Teta Emi Sapitri; Usman Malik (Universitas Riau, 2020)
Identification of groundwater at Graha Mustamindo Permai 3 Housing Complex, Rimba Panjang Village, District Tambang, Kampar Regency, Riau Province has been done. The method used in this study is the geoelectric method with Schlumberger configuration. Identification of the aquifer layer was carried out on 2 tracking lines with a length of 100 meters. Measurement data were processed using software Progress. The results of data processing of track 1 and 2 show a maximum depth of 35 meters. The results of aquifer interpretation on track 1 are at depth of (3.90–11,13) meters with a resistivity value of 246.51 Ω.m. Track 2 is at a depth of (7.43–14.66) meters with a resistivity value of 142.15 Ω.m. Soil water samples were tested for pH parameters. All water samples have acid levels with an average pH of 5. So that it can cause rust an inner surface of water pipe resulting smelly water therefore the water cannot be consumed by the people.